2017
DOI: 10.4082/kjfm.2017.38.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Current Status, and Barriers toward Healthcare Worker Vaccination among Family Medicine Resident Participants in a Web-Based Survey in Korea

Abstract: BackgroundWe investigated the knowledge, status, and barriers toward healthcare workers receiving vaccinations among Korean family medicine residents. To date, a systematic study has not been conducted among medical practitioners examining these variables.MethodsA web-based, anonymous, self-administered questionnaire was distributed to all 942 family medicine residents working in 123 training hospitals in Korea. A multiple logistic regression analysis was performed to investigate factors affecting vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…Our survey revealed that the sources of information regarding protective precautions were college Although the order varies in different reports, in concordance with our findings, the leading three reasons for not being vaccinated were disbelief in personal need, doubts related to efficacy and side effects (10,25,26). 234 (17.8%) of our participants declared their concerns but could not give evidence for the side effects.…”
Section: Discussionsupporting
confidence: 88%
“…Our survey revealed that the sources of information regarding protective precautions were college Although the order varies in different reports, in concordance with our findings, the leading three reasons for not being vaccinated were disbelief in personal need, doubts related to efficacy and side effects (10,25,26). 234 (17.8%) of our participants declared their concerns but could not give evidence for the side effects.…”
Section: Discussionsupporting
confidence: 88%
“… 18 A survey conducted with resident doctors of the specialty Family Medicine in Seoul, South Korea, pointed out that although coverage for influenza vaccine was good (83.0%), the knowledge about all vaccines recommended for health professionals by the local infectious society was very low (9.9%). 19 …”
Section: Discussionmentioning
confidence: 99%
“…Murray and Skull (2002) reported that, of HCWs born after 1970 in Australia, 21% reported not having had a MMR vaccination. The MMR vaccination rate of Family Medicine Residents in Korea was 15.9% (Ko et al , ). In the present study, nurses’ MMR non‐vaccination rate was slightly higher than in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through this it was discovered that nursing patients with measles increased the nurses’ awareness of the need for measles vaccination. According to Ko et al (), the most common barrier for MMR vaccination was that the participants felt that they had a small possibility of infection. The prevalence of measles in non‐immune HCWs is low.…”
Section: Discussionmentioning
confidence: 99%